Strategies for Surgical Management of Large, Stiff Spinal Deformities in Children. Issue 4 (April 2017) - Neal, Kevin M.; Siegall, Evan
Abstract : Management of large, severe, stiff spinal deformities in children can be challenging. Adjunctive treatments used in conjunction with spinal osteotomy, instrumentation, and fusion can improve the ultimate degree of deformity correction. These adjunctive treatments include preoperative halo-gravity traction, intraoperative halo-femoral traction, temporary internal spinal distraction, and anterior spinal release. Each of these techniques has unique indications and individual risks. When the appropriate protocols are followed, these techniques can be safe and efficacious.